Propagación vegetativa por estaquillas de Ceiba pentandra “lupuna” con dosis de ácido indolbutírico en sustratos agrícolas en Puerto Almendra, Loreto, Perú, 2023 - Macedo Lopez, Mirian Eugenia (2024)
Ceiba pentandra, known for its high economic value in the manufacture of plywood, faces risks due to unsustainable exploitation that affects its natural reproduction by preventing the production of flowers, fruits and seeds after logging. Therefore, it is crucial to develop new vegetative propagation techniques, such as propagation by cuttings, in order to conserve and sustainably use this species. The aim of this thesis was to evaluate the vegetative propagation by cuttings of C. pentandra in tubetes obtained from the yew orchard of the Centre of Provenance of Agricultural and Forestry Species of the Faculty of Forestry Sciences UNAP. A total of 192 cuttings, two types of agricultural substrates (calcined rice husk and agricultural perlite) and four doses of AIB (0 ppm, 2000 ppm, 4000 ppm and 6000 ppm) were used, distributed in eight treatments. The result shows that agricultural perlite significantly favored callus formation and rooting of cuttings compared to calcined rice husk. However, there is no statistical significance between the different doses of AIB in any of the substrates. In terms of survival, higher rates were recorded for cuttings grown on agricultural perlite at D0 ppm (54.2%) and D2000 ppm (45%), while the lowest rates were observed on calcined rice husk at 4000 ppm (29.2%), 0 ppm (20.8%) and 12% at 6000 and at 4000 all cuttings died. These findings highlight the importance of substrate in the successful propagation of C. pentandra cuttings and suggest that the dose of AIB did not significantly influence the results obtained.